Rozległa torbiel korzeniowa żuchwy leczona metodą dwuetapową - opis przypadku = Large residual cyst in mandible treated by two-step method - case report - Piotr Osica; Karolina Osica; Aleksandra Szczepkowska; Anna Janas-Naze (Kazimierz Wielki University, 2017)
Osica Piotr, Osica Karolina, Szczepkowska Aleksandra, Janas-Naze Anna. Rozległa torbiel korzeniowa żuchwy leczona metodą dwuetapową - opis przypadku = Large residual cyst in mandible treated by two-step method - case report. Journal of Education, Health and Sport. 2016;6(11):444-455. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.174791 http://ojs.ukw.edu.pl/index.php/johs/article/view/4019       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 27.11.2016.       Rozległa torbiel korzeniowa żuchwy leczona metodą dwuetapową - opis przypadku Large residual cyst in mandible treated by two-step method - case report   Piotr Osica1, Karolina Osica2, Aleksandra Szczepkowska1, Anna Janas-Naze1   1Zakład  Chirurgii Stomatologicznej UM w Łodzi Kierownik: dr hab. n. med. prof. nadzw. Anna Janas-Naze 2Poradnia Stomatologii Ogólnej z Izbą Przyjęć CSK IS UM w Łodzi Kierownik: lek. stom. Ewa Malenta-Markiewicz   Adres do korespondencji: Piotr Osica Zakład Chirurgii Stomatologicznej UM w Łodzi 92-213 Łódź, ul. Pomorska 251 e-mail: piotr.osica@umed.lodz.pl tel. 42 675 75 71   Praca finansowana przez Uniwersytet Medyczny w Łodzi w ramach działalności statutowej nr 503/2-163-01/503-21-001   Streszczenie W pracy opisano przypadek leczenia dwuetapowego rozległej torbieli korzeniowej w żuchwie u 58 letniego pacjenta.   Słowa kluczowe: torbiel korzeniowa, obturator, metoda dwuetapowa   Abstract The article presents the case of 58 year old man with large radicular cyst in mandible.   Key words: radicular cyst, obturator, two-step method